Pengaruh Penggunaan Platform Quizizz Terhadap Partisipasi Kelas dalam Pembelajaran Mufradat - Dewi, Annisa Rahmawati; Alawiyah, N. Lalah; Raswan, Raswan (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This study aims to reveal the impact of the Quizizz platform on enhancing classroom participation in Mufradat learning. The focus of this research is on the issue of low student participation in Mufradat learning at MI Al-Mursyidiyah Pamulang, which is often perceived as boring and uninteresting. This study employs a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. Data were collected through observation, documentation and classroom participation questionnaires. The research subjects consisted of 32 students from class six B of MI Al-Mursyidiyah. Data analysis was conducted using the